The invisible sublime : theories of art in Carl Einstein's later writings - Creighton, Nicola (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2004)
This study is a contribution to research on Carl Einstein (1885-1940), German-Jewish writer, critic and historian of art. It concentrates on Carl Einstein’s later work, from Die Kunst des 20. Jahrhunderts, his contribution to the Propylden art encyclopedia series, first published in 1926, to Die Fabrikation der Fiktionen, most likely written between 1932 and 1936, paying attention also to unpublished archival material. The thesis is that, while the role of dialectics has been played down in much of the secondary literature, Einstein’s writing on aesthetics and on the history of art exhibits a pervasive dialectical use of concepts, reconstructing traditional aesthetic theory from within. This is not to deny the dismantling from without, i.e. the impact of other disciplines such as ethnology, sociology and psychology, on the development of Einstein's theories (the plural is required as substantial shifts in his concepts engender distinct, rivaling theories). Nor is it simply to write him back into a discourse he sought, sometimes painstakingly, sometimes rashly, to write himself out of: the discourse of aesthetics in its peculiarly German variety, with a strong emphasis on epistemology and an even stronger emphasis on ethics. It is, rather, to attempt to understand the way in which some of his key concepts shift in valuation between his texts. One such concept is the 'tectonic'. With reference to this concept and its dialectical counterpart, the 'hallucinative interval', theories of the sublime, starting with Kant, are probed.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin